Pengaruh Latihan Ballhandling Dan Latihan Menggunakan Bolakecil Terhadap Keterampilan Dribbling Bolabasket Smp Hayatan Thayyibah - Asytar Mauluda Sudianto; Titis Nurina; Firman Septiadi (FKIP Universitas Muhammadiyah Sukabumi, 2019)
The problem of this study is that there is still a lack of students' skills in dribbling, such as many violations when dribbling (illegal dribbling), still seeing the ball when dribbling (not automatic), this study aims to determine the results of dribbling skills after being treated in the form of ballhandling and training using a small ball at Hayatan Thayyiban Middle School. The design used in this study is experimental, data collection using tests, the instrument used is a test of dribbling ability, which is a test to determine students' ability to dribbling basketball. Sample in the study were 22 extracurricular students and divided into two groups, group A (ballhandling) and group B (using small balls), data analysis techniques used t-test analysis (t test), through tests of normality and homogeneity. The results of the hypothesis testing of the t-test 1) There is the effect of ballhandling exercises with t-count (3.84)> t table (1.72) at the significance level Î± 0.05. an increase of 79 points from 120 to 145. 2) There is an effect of using small balls exercises with t-count (3.79)> t table (1.72) at a significant level of Î± 0.05. an increase of 81 points from 727 to 808. The conclusions in this study are: 1) there is the effect of ballhandling training on basketball dribbling skills at Hayatan Thayyibah Middle School. 2) there is the effect of using training on using small balls on Hayatan Thayyibah basketball dribbling skills. 3) training in using small balls has more influence on basketball dribbling skills in Hayatan Thayyibah junior high school extracurricular.